1990
DOI: 10.1016/s0006-3495(90)82595-9
|View full text |Cite
|
Sign up to set email alerts
|

Sodium channel activation mechanisms. Insights from deuterium oxide substitution

Abstract: Schauf and Bullock (1979. Biophys. J. 27:193-208; 1982. Biophys. J. 37:441-452), using Myxicola giant axons, demonstrated that solvent substitution with deuterium oxide (D2O) significantly affects both sodium channel activation and inactivation kinetics without corresponding changes in gating current or tail current rates. They concluded that (a) no significant component of gating current derives from the final channel opening step, and (b) channels must deactivate (during tail currents) by a different pathway… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
32
0

Year Published

1990
1990
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 36 publications
9
32
0
Order By: Relevance
“…On the other hand, substitution of deuterium oxide for water in the internal perfusate of voltage-clamped crayfish giant axons slows activation of sodium current without any corresponding change in deactivation rate or detectable effect on gating currents (Alicata et al, 1990). These observations confirmed the earlier findings A part of this work has been presented in preliminary form (see Starkus and Rayner, 1987;Rayner and Starkus, 1991).…”
Section: Introductionsupporting
confidence: 86%
“…On the other hand, substitution of deuterium oxide for water in the internal perfusate of voltage-clamped crayfish giant axons slows activation of sodium current without any corresponding change in deactivation rate or detectable effect on gating currents (Alicata et al, 1990). These observations confirmed the earlier findings A part of this work has been presented in preliminary form (see Starkus and Rayner, 1987;Rayner and Starkus, 1991).…”
Section: Introductionsupporting
confidence: 86%
“…The voltageindependent transition step involves a measurable increase in the volume available to water and is therefore termed the solvent-sensitive transition (Zimmerberg et al, 1990). Based on the experiments with substitution of deuterium oxide for water, Alicata et al (1990) concluded that the sodium channels could activate via two alternative routes, a solvent-sensitive pathway or a solvent-insensitive pathway, depending on initial conditions. The multiple parallel activation mechanisms observed in the sodium channel are inconsistent with a linear sequential model for channel gating, and cyclic gating models have been proposed for activation of the sodium channel (Rayner et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Given that the cyclical model shown in Fig. 8 applies to activation of the DHP-sensitive Ca channels as well as the Na channel (Alicata et al, 1990;Starkus and Rayner, 1991) and K channel (Zagotta et al, 1994;and Starkus et al, 1995), it is reasonable to propose that voltagesensitive gating transitions occur early in the Ca channel activation sequence and that it is these processes which could underlie the role of the voltage sensor and yield the rapid E-C coupling in skeletal muscle, through either electrostatic or allosteric linkage to the ryanodine receptor Ca release channel.…”
Section: Dhp Receptors As Fast E-c Coupling Voltage Sensor and Slow mentioning
confidence: 99%
“…In the state diagrams shown in ¢gure 1a,b the transition from AAAA to AAAA* cannot be identi¢ed as the voltage-independent hydration step that must precede opening at some point (Rayner et al 1993), because this would be incompatible with the evidence on the e¡ect of D 2 O on the gating system. It was shown by Conti & Palmieri (1968) that in heavy water the kinetics of both opening and closing in the squid giant axon were slowed by a factor of 1.4, but Meves (1974) subsequently found that D 2 O had little or no e¡ect on the sodium gating current, as was con¢rmed for Myxicola axons by Schauf & Bullock (1979), and most recently for cray¢sh axons by Alicata et al (1990), leading inescapably to the conclusion that the main steps which generate the gating current must precede the principal D 2 O-sensitive transition. It is consequently proposed that hydration mainly takes place after arrival of the channel at the state shown as BBBA, taking it to the initial open state BBBA, though a subsidiary route via a closed hydrated state AAAA has been included.…”
Section: The Structure and Function Of The S4 Voltage-sensorsmentioning
confidence: 94%